(untitled) (Nexus International Journal of Science and Education, 2024)
The study aimed to understand teachers' perceptions of using digital technology in their classrooms. The study focuses on three main themes: attitudes and beliefs, professional development, and effective professional development programs. Additionally, the study explores how teachers cope with the challenges of using digital technology in their instruction through Pedagogical Approaches, Challenges and Barriers, and Student Outcomes, the study drawn educational insights from its findings regarding digital pedagogy and instructional practices, contextual factors, and differentiated instruction. The research disclosed the findings based on the data gathered from of ten (10) participant’s line-up of public elementary school faculty. Addressing these areas can contribute significantly to the successful integration of digital technology in classroom instruction, ultimately enhancing the quality of education provided to students. The study's findings have important implications for various aspects of education, including teacher training programs, professional development initiatives, pedagogical innovation, addressing challenges and barriers faced by teachers when integrating technology into their teaching methods, improving student outcomes through effective use of digital tools, influencing educational policies related to technology integration in schools at different. Ultimately, this research can contribute significantly towards enhancing education quality provided by successfully integrating digital technologies into classroom instructions which prepares students in an increasingly technological world.